Study of Traditional Chinese Medicine to Treat Skin Diseases and Improve Skin Health - Shahrajabian, Mohamad Hesam; Sun, Wenli (Current Nutrition & Food Science, 2025)
IntroductionHerbal therapies and application of medicinal plants have been applied for the prevention and treatment of skin conditions for decades in different parts of the world, especially in China. The most common groups for which medicinal herbs and plants are used are acne, psoriasis, dermatitis and wart.MethodsThis review aims to promote the utilization of traditional Chinese medicine for different skin diseases by considering the importance of medicinal plants according to their medicinal properties, lastly, future challenges and research directions are discussed. The most important chemical components for treatment of acne, atopic dermatitis, skin cancer, wart, and hives are lupeol, artemetin, hydroquinone, hypericin, epicatechin, curcumin, schizandrin, lobelanidine, celacinnine, glycyrrhizin, licoflavanone, isoliquiritigenin, glabridin, liquiritin, liquiritigenin, glycyrrhisoflavone, cyanidin, baicalin, cupressuflavone, paeonol, hinokiflavone, resveratrol, silibinin. Some of the most important medicinal plants used for wound healing are Acacia mellifera Benth., Acacia erioloba Edgew, Aloe arborescens Mill., Capparis tomentosa Lam., Barleria rigida Spreng., Centella asiatica (L.) Urb., Bridelia micrantha Baill., Datura stamonium L., Melianthus major L., Ficus natalensis Hochst., and Mentha longifolia L.ResultsTraditional Chinese medicinal plants which have been used in treatment of acne are Scutellaria baicalensis, Sapindus mukorossi Gaertn, Arctium lappa, Polygonum cuspidatum, Epimedium brevicornum, Rosa damascene, Ilex paraguariensis, Glycyrrhiza spp., and Radix angelicae formosanae, while some prescriptions such as Sanhuang anti-itching lotion, Chushi decoction, Xiaofeng power, Xiao Feng Dan formular and Jianpi Chushi decoction should be considered for treatment of eczema. The extract of Helianthus annuus extract, Terminalia chebula extract, Olea europaea leaf extract, Spirodela polyrhiza extract, and Juniperus rigida fruit are also important for the treatment of eczema.ConclusionThe authorization and validations only indicate the significance and importance of traditional Chinese medicine in treating skin diseases, but also clarify its uniqueness and importance.
Keywords: skin health